The effect of changing the CEO on the company’s share price : Event study in Helsinki Stock Exchange - Viitaniemi, Valtteri (My University, 2024)
This study examines the impact of CEO changes on the stock prices of companies listed on the Helsinki Stock Exchange, focusing on market reactions and testing the semi-strong form of the Efficient Market Hypothesis (EMH). Using an event study methodology, the research analyses stock price reactions over a five-day event window around CEO change announcements and estimates abnormal returns based on the market model. The findings reveal that CEO changes in Helsinki Stock Exchange lead to negative stock price reaction, with abnormal returns being statistically significant in specific event windows. The results suggest that the Finnish stock market exhibits a measurable reaction to CEO changes, indicating that such announcements are perceived as important signals by investors. Additionally, the study found out delay in market reaction as announcement days abnormal return wasn’t statistically significant while the abnormal return day after the announcement was. That might signal slight inefficiency in semi-strong form of the Efficient Market Hypothesis, assessing the market’s efficiency in processing new information. This research contributes to the understanding of how leadership changes affect investor behaviour in the Finnish stock market and provides insights into market efficiency. The findings have implications for corporate governance, investor decision-making, and regulatory considerations, particularly in markets characterized by smaller size and liquidity.
Keywords: Chief executive officer, CEO change, Market efficiency